A construção discursiva do trabalho feminino em revistas: uma comparação entre Jornal das Moças e Claudia - Azevêdo, Jeany Santos De Carvalho (2018)
The present research constitutes a study about the discursive construction of feminine work based on written and imagetic texts published in Jornal das Moças (fifties of the twentieth century) and Claudia (from 2010 to 2015 of the twenty-first century) magazines. These magazines for women talk about subjects considered important to this public in their determined conditions of production. This theme is relevant because of the necessity of observing how it is constructed the discourse about women and work as well as it provides the opportunity to comprehend the reason why some discourses about the position women can/have to occupy in the society are reproduced/silenced nowadays, mainly concerning outdoor work. The theoretical scope of the research is centered on Pêcheux’s Discourse Analyses, specially the studies of Orlandi (2007, 2015) and Pêcheux (1993, 2006). Thus, some basic assumptions of this theory are relevant to this study, such as: imaginary, discursive and ideological formations, which guide what it is said about women in the magazines analyzed, as well as the already-said about women that composes the interdiscourse. Based on the corpus selected from Jornal das Moças and Claudia magazines, it was observed the discursive sequences and imagetic which relate women and work, applying the theoretic-methodological apparatus of Pêcheux’s Discourse Analysis to this data. It is important to highlight that the results show that there is a difference on the construction of women in the magazines. While the publications from the fifties discursed women at home and in some professions which were in extension of the housework, Claudia magazine modifies the bias showing women in many professions, but still struggling for salary equality and for respect and appreciation when they occupy leadership positions in the companies. Although it is important to highlight that even when discursing the woman in different positions, the magazine, in the analyzed material, still give more emphasis to mother, wife and housewife positions, showing that the already-said about women from the most remote periods still resound in nowadays discourses, indicating that there is a tension between work and maternity.